The Role of the Village Government in Minimizing Early Marriage in Bujak Village, Batukliang Subdistrict, Central Lombok Regency - Putri, Wina Rahma; Mustari, Mohamad; Hadi, M. Samsul; Kurniawansyah, Edy (Jurnal Penelitian Medan Agama, 2025)
This research is driven by the prevalence of early marriage in Bujak Village, as evidenced by data from the past five years (2019–2024). Based on the data collected, several underlying factors contribute to the occurrence of early marriage, including economic factors, customary practices, social factors, and cultural influences, all of which play a role in the persistence of early marriage in Bujak Village, Batukliang Subdistrict, Central Lombok. This study employs a qualitative research method using a case study approach, aiming to explore in depth the cases of early marriage that occur in Bujak Village, Batukliang Subdistrict, Central Lombok.